DEVELOPMENT OF EDUCATIONAL INSTITUTIONS WITHIN THE NETWORK INTERACTION - Evgeny M. Dorozhkin; Nataliya N. Davydova (Высшее образование в России, 2022)
The paper describes the possibilities of using network-based approach in management of the development of modern educational institutions of general and vocational education, which enables to supplement competitive relations with cooperation and construct conjointly a regional educational network.